Factors influencing the color laser marking (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In recent years, conventional techniques of marking on some parts of different work pieces, as well as on packages with color printing are increasingly being displaced by laser color marking. Colored marking of stainless steel could be realized by the process annealing. The advantages offered by the new technology are in greater accuracy, speed, flexibility and high amount of recorded information per unit area (bar and matrix codes).In the report are discussed and analyzed the factors influencing on the specific to the process of laser color marking at the products of CrNi steel.  The study was conducted using a commercially available industrial pulsed fiber laser. Presents the results of the measurements and analysis of the influence of laser process parameters on the color contrasting obtained. In this case, the relevant parameter, the field of high frequencies and low pulse energy were examined. The present thesis describes studies a properties of the laser radiation, such as, pulse width, average power, the intensity and beam diameter.